AUDIT EXEMPTION FOR SMALL AND MEDIUM ENTERPRISES: PERCEPTIONS OF MALAYSIAN AUDITORS - Hasnah Haron; Ishak Ismail; Yuvaraj Ganesan; Zulhawati Hamzah (Asian Academy of Management Journal, 2016)
The objective of the study is to examine audit firm size, the provision of non-audit services (NAS) and audit tenure as factors that influence the likelihood that an auditor agrees with allowing audit exemption. This study employs a 2 × 2 × 2 within-subject experimental design. Respondent auditors were required to evaluate 8 case scenarios. A total of 79 questionnaires were returned and used for data analysis. General Linear Measurement (Repeat Measure) was used to analyse the data. The study found that an audit firm size has a significant impact on the likelihood that an auditor agrees with offering audit exemption. The larger the size of the firm, the greater is the likelihood of agreeing with allowing audit exemption. Therefore, it is suggested that small audit firms (with 5 or fewer employees) merge and focus on activities that contribute more added value such as consultancy. In so doing, auditors from these firms would be required to improve their knowledge and capacity by offering these services and not merely focusing on traditional audit work for SMEs. This is because SMEs are known to have limited resources and capacity and thus would be expected to have poor internal control. The requirement of a mandatory audit for such firms might lead auditors to compromise their independence. Thus, the government and the Malaysian Institute of Accountant (MIA) should help small audit firms to develop the necessary knowledge, skills and competencies to perform non-audit services.